Prevalence and risk factors of primary open-angle glaucoma in a city of Eastern China: a population-based study in Pudong New District, Shanghai. Issue 1 (December 2015) - He, Jiangnan; Zou, Haidong; Lee, Richard; Tong, Xiaowei; Tang, Wenli; Zhang, Yi; Zhao, Rong; Ge, Ling
Abstract Background The aim of the present study was to investigate the prevalence and characteristics of primary open-angle glaucoma among the urban population of Pudong New District, Shanghai. Methods Three residents' committees were randomly selected from Pudong New District, and residents aged 50 and older were screened for primary open-angle glaucoma (POAG) from March to April 2011. In remote screening, the tests on visual acuity, refraction, intraocular pressure (IOP), and the photographs of anterior segment and fundus were used to identify POAG suspect. The suspected subjects were then reexamined with the tests on IOP, gonioscopy, Humphrey visual field test, and retinal nerve fiber layer (RNFL) thickness by optical coherence tomography (OCT). POAG was diagnosed according to the criteria defined by International Society for Geographic and Epidemiological Ophthalmology (ISGEO). Finally, POAG risk factors were evaluated using logistic regression analysis. Results A total of 2528 citizens out of 3, 146 eligible residents (80.36 %) participated in this study. Among the citizens, 72 were diagnosed to have POAG, giving the crude prevalence rate of 2.85 % (95 % CI:2.20 %–3.50 %) in general and age- and gender-adjusted prevalence rate of 2.8 % (95 % CI: 2.78 %–2.83 %). Among the 72 POAG patients, only 22 cases had IOP exceeding 21 mmHg while other 50 cases had IOP of 21 mmHg or less; nine cases had one eye blind (12.5 %). Intriguingly, only eight cases (11.11 %) had been diagnosed with POAG before this screening. Conclusions More efforts are required for early screening and education on POAG in communities, especially in a POAG high-risk population.